NILAI STRATEGIS INDIAN OCEAN RIM ASSOCIATION BAGI INDONESIA DALAM PENEREPAN POROS MARITIM TAHUN 2015 - Satya Wira Wicaksana; Idjang Tjarsono (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Since Joko Widodo inaugurated as the President of Indonesia, Indonesia made a movement of the policy based on Maritime Axis concept. The concept means to recalling the nature of Indonesia’s paradigm in case of the nation is the archipelagic state. In the process of the implementation of the concept, particularly on 2015 October, Indonesia officially became the chairman of Indian Ocean Rim Association (IORA). The implementation of Maritime Axis had politically aided by these two correlated entities.This research is a descriptive-analytic that aims to explain the strategic values of IORA and theoretically using Regional Security Complex Theory by Barry Buzan that describes the complexity in a region. In realism realm, the RSCT is utilized to as one of substructure and has role in theoretical precisely in international system case.The equilibrium of Maritime Axis Pilar and 6 Priorities of IORA concluded that IORA has strategic values in implementing Maritime Axis concept for Indonesia. The statement hypothetically supports by several reasons such as Indonesia could use IORA for rebuilding the maritime culture, guarding the sea resources, maritime diplomacy, and building the maritime power that accumulated by three realms such as political and security, economy, and socio-cultural.Keywords: IORA, Indian Ocean, Political and Security, International Economy, RSCT